THE QUALITY OF BALI AND WAGYU BEEF AT THE COLD STORAGE - Agustina, Kadek Karang; Sembiring, Sonia Dewi Citra; Suada, I Ketut (Buletin Veteriner Udayana, 2019)
These study aims were to determine the quality of bali beef and Wagyu beef stored at 4oC. This study used a completely randomized factorial pattern design. Meat quality parameters studied included pH, water content, water holding capacity, and texture. The results showed that the pH value of Wagyu beef and bali beef increased during storage at cold temperatures. While the water content, water binding capacity, and texture of both types of meat have decreased. Significant changes occurred in observations of the fourth day. It can be concluded that the storage of Wagyu and bali beef at 4oC was not effective for a period of more than 3 days.